ENTERAL TUBE FEEDING IN ACUTE PANCREATITIS AND ITS COMPLICATIONS - Kolosovych, I.V.; Hanol, I.V.; Cherepenko, I.V. (World of Medicine and Biology, 2021)
The use of early enteral tube feeding in patients with acute pancreatitis improves the course of the disease, but is dangerous for the development of intestinal complications. The aim of the study was to improve the results of comprehensive treatment of patients with acute pancreatitis by preventing complications of enteral tube feeding. The clinical material is based on the results of treatment of 79 patients with acute pancreatitis who received enteral tube feeding and were divided into a comparison group and the main group (in addition to the tube received a emulsion of simethicone). It was found that the recovery of intestinal absorption (at the peak of exacerbation of the inflammatory process of the pancreas or in the early postoperative period) occurs at 2.2±0.3 days, and membrane digestion – at 4.1±0.5 days from the start of treatment. The use of simethicone emulsion for the prevention of intestinal complications on the background of enteral tube feeding reduced the incidence of intestinal complications in the first two days after treatment by 32.1 % (p=0.001), for 3–4 days – by 36.4 % (p=0.0004) and 7 days – by 23.3 % (p=0.004).
Keywords: pancreatitis; complications; enteral nutrition; membrane digestion; intestinal absorption; prevention